2020
DOI: 10.1177/0036933020936274
|View full text |Cite
|
Sign up to set email alerts
|

The value of non-invasive computed tomography coronary angiography in imaging patients with coronary artery bypass grafts

Abstract: Introduction Invasive coronary angiography (ICA) is associated with higher complication rates in patients following coronary artery bypass surgery (CABG). CT coronary angiography (CTCA) has emerged as an attractive alternative. We assessed the impact of CTCA on subsequent ICA. Methods We identified 213 CABG patients undergoing CTCA between 2015 and 2018. In 151 the indication was suspected recurrence of angina. We then identified patients undergoing ICA within 1 year of CTCA. Results CTCA obviated the need for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Previous observational studies have suggested upfront CTCA may reduce the exposure of patients to contrast, radiation, and the clinical risks of invasive procedures. 14 , 15 , 21 A recently presented RCT (GREECE [Computed Tomography Coronary Angiography in Patients With a Previous Coronary Artery Bypass Graft Surgery Trial]) has provided some preliminary data. 22 , 23 In GREECE, 153 patients with previous CABG and a clinical indication for coronary angiography were randomized to CTCA+ICA (n=84) or ICA alone (n=69).…”
Section: Discussionmentioning
confidence: 99%
“…Previous observational studies have suggested upfront CTCA may reduce the exposure of patients to contrast, radiation, and the clinical risks of invasive procedures. 14 , 15 , 21 A recently presented RCT (GREECE [Computed Tomography Coronary Angiography in Patients With a Previous Coronary Artery Bypass Graft Surgery Trial]) has provided some preliminary data. 22 , 23 In GREECE, 153 patients with previous CABG and a clinical indication for coronary angiography were randomized to CTCA+ICA (n=84) or ICA alone (n=69).…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of SMJ, Atrah Hasan 1 provides a background to cytokine storm and strategy to deal with. Krysztofiak et al 2 report experience of non-invasive CT scan in assessing bypass graft condition and Demir Gu¨ndo gmus¸et al 3 describe coronary intervention in elderly population. These publications enhance our understanding of cardiovascular disease which remains one of the major killers in Scotland and world over.…”
Section: Ghulam Nabimentioning
confidence: 99%